Lejja Natural Tourism Object Development Strategy, Marioriawa District, Soppeng Regency - Nur, Andi Cudai; Anugrah, Andri; Purna, Zarni Adia (Universitas Negeri Makassar, 2023)
This study aims to determine the development strategy of Lejja Nature Tourism Object, Marioriawa District, Soppeng Regency. This type of research is a qualitative research with data collection techniques of observation, interviews, and documentation. The data analysis technique uses SWOT analysis which is considered to be able to facilitate researchers to formulate strategies for developing Lejja Nature Tourism Objects, Marioriawa District, Soppeng Regency.The result of this study indicate that the development of lejja nature tourism object, Marioriawa district, Soppeng regency has several factors that support its development, namely the promotion strategy, while the form of promotion carried out by the perusda is by using mass media and word of mounth of visitors who have visited. For strategy accessibility. The management has improved access to tourist attractions. So that the trip is not disturbed anymore. For regional tourism area strategy. Lejja nature tourism is a protected forest area so that apart from swimming we can also enjoy the coolnes of the surrounding nature. And as for the result of the swot analysis of the strength,weakness,opportunity,and threat factor were greate than other factors so that the strategy for developing natural tourism objects could be maximized by developing strategies that maximize the strengths and opportunities of the object. Lejja nature tourism, Marioriawa district, soppeng regency.